FRACTURE PROPERTIES OF PIANO STRINGS ON THE V-BAR - HU QianRu; ZHUAN Xin (Jixie qiangdu)
V-bar is the major fracture location of piano strings. It’s important to analysis the fracture mechanism of the string in the V-bar for the design and adjustment of the piano string. In this paper,a systematic analysis was performed for the decoration form,loaded modes and vibration of the strings. Three fractures of piano strings under the same key number,figure number and known service life was selected as the objects. A comparative analysis was performed to observe the fracture morphology with the Scanning Electron Microscopes（ SEM）. It is shown that surface abrasion arises because of the wear between the string and V-bar,which causes the stress concentration in this area. The repeated bending loads during playing lead to fatigue initiation and propagation over the string cross section. The final fracture occurred when the stresses exceed the breaking strength of the string. The fibrous fracture was observed under the SEM.